PENGARUH KOMITMEN ORGANISASI, ETIKA ORGANISASI, KEADILAN KOMPENSASI, DAN SISTEM PENGENDALIAN INTERNAL TERHADAP FRAUD (STUDI EMPIRIS PADA SKPD PEMERINTAH KOTA LHOKSEUMAWE) - Albar, Teuku Meurah; Fitri, Fauziah Aida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The purpose of this research is to examine the effect of organizational commitment, organizational ethics, compensation justice, and internal control system on fraud at SKPD Lhokseumawe Government. The population of this research is all units of SKPD in the city of Lhokseumawe government which totaling 31 of government departments, agencies, and offices (155 respondents). The qualified respondents consist of 152 questionnaire. Data collection techniques were conducted with questionnaires. The results of this research shown that simultaneously and partially, organizational commitment, organizational ethics, compensation justice, and internal control system have a negative effect on fraud at SKPD Lhokseumawe government.